Close the divide [videorecording (DVD)] - Acton, Tom; Rose, Eric (Common Ground Film Ltd., 2024)
Close The Divide unveils a gripping journey to bridge the deep divide on climate change, revealing how uniting diverse perspectives can spark innovative solutions to our planet's most pressing challenge. There is mass confusion in the world relating to climate change. A growing gap between reality and perception has created viewpoints often based on emotion rather than fact.